Local imitations of imported fine tablewares from Southern Pannonia: The production of the Flavian and post-Flavian period - Leleković, Tino (Rei Cretariae Romanae Fautorum Acta, 2017)
Excavations of Roman sites in the Croatian part of Pannonia have revealed large quantities of fine pottery of local origin, the majority of which are imitations of forms deriving from imported terra sigillata. Collected examples of such imitations typologically can be divided into those that imitate the ‘Italian-style’ sigillata of the Flavian and Trajanic/Hadrianic periods, and those which imitate relief-decorated sigillata from the Central Gaul and Rhine regions in the Antonine and post-Antonine periods. Recent excavations showed that these finds, as well as by their typological elements, can also be chronologically distinguished according to the stratigraphy. On the basis of the documented contexts it can be confirmed that imitations of ‘Italian-style’ sigillata precede that which imitates Gaulish and Germanic prototypes. The imitation of sigillata from the Flavian period has shown to be the first example of fine table ware with a distinctive Pannonian fabric, so that it can be regarded as the first stage of development of the Pannonian pottery production. It can be assumed that this is how Pannonische Glanztonware (PGW)was created.